UPAYA PENINGKATAN KESEJAHTERAAN KELUARGA MELALUI BUDIDAYA RUMPUT LAUT (Studi Di Desa Kolese Kecamatan Pasikolaga Kabupaten Muna) - Ghalib, La Ode Muhamad; Sarmadan, Sarmadan; Tanzil, Tanzil (Universitas Halu Oleo, 2020)
This study aims to analyze how the efforts to improve family welfare through seaweed cultivation in college villages. This type of research is qualitative descriptive research. Data collection techniques were carried out by means of observation, interviews and documentation with 8 research informants in the community of Kolese Village, Pasikolaga District.The results of this study are efforts to improve family welfare through seaweed cultivation, namely increasing economic income by fulfilling family needs and being able to pay for children's schooling. With the existence of a joint business group, it is one of the efforts that can improve family welfare. The results achieved by the people of Kolese Village, Pasikolaga District, Muna Regency in an effort to increase welfare welfare through seaweed cultivation have been overcome by cultivating seaweed.